Wood variation in physico-mechanical properties of Dalbergia sissoo Roxb. ex DC. from local markets of Himachal Pradesh - Sunny, Pavin Praize; Dutt, Bhupender; Sharma, Kulwant Rai; Dhiman, Bandana; Sumthane, Yogesh Yadavao (Journal of Tropical Agriculture, 2019)
Attempt was made to evaluate the wood variation in Dalbergia sissoo (shisham) from the local markets of Himachal Pradesh. The highest moisture content (20.17%) was observed in the wood samples of Nalagarh site. Highest specific gravity of 0.644 was observed in Dattowal and lowest (0.748) in Nalagarh site. Significant variation in mechanical properties was observed for all the studied parameters. The maximum bending strength was recorded in Baroh and Sundernagar site (0.006 kN/mm2) and maximum tensile strength (0.094 kN/mm2) was noticed in the wood samples from Baroh site. The maximum compressive strength parallel to grain (0.069 kN/mm2) was observed in Kangu site and maximum compressive strength perpendicular to grain (0.038 kN/mm2) was found in Baroh site. The maximum modulus of elasticity parallel to grain (0.231 kN/mm2) was recorded in Ghumarwin and maximum modulus of elasticity perpendicular to grain (1.653 kN/mm2) was noticed in wood samples of Galore site. The greater modulus of elasticity due to tension and bending was found in the wood samples of the sites Baroh (2.876 kN/mm2) and Kangu (10.369 kN/mm2) respectively. The maximum bending modulus of rupture was observed in the wood samples from the sites of Sundernagar (0.116 kN/mm2) and for teak was found to be 0.323 kN/mm2. The maximum elongation for shisham wood samples for bending was found in Nalagarh site (0.039 mm) and for tension in the site of Sarahan (0.033 mm). The mechanical properties of shisham wood were compared with standard teak wood samples and it was found that the wood samples of shisham were superior in some mechanical properties.